Częstochowa - aksjologiczny obraz miasta promowany w miesięczniku "Jasne, że Częstochowa" = Częstochowa - an axiological image of the city promoted in the "Jasne, że Częstochowa" month periodical - Jaros, Violetta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this sketch is to characterize the axiological image of Częstochowa promoted in the "Jasne, że Częstochowa" month periodical in the light of cultural and entertainment activities and socio-economic activities undertaken by various entities, as well as the city?s assets and potential of its inhabitants, presented in a free periodical published by the Department of Culture, Promotion and Sport of the City Office, where it has been combined with a description of the structure of the magazine as a functional tool of territorial marketing of the city.
Keywords: wartości; wizerunek miasta; czasopismo lokalne; values; city image; city periodical